Acid-base and blood gas status during bovine endotoxic shock and after i/v infusion of hypertonic saline solution in buffalo calves - Singh, D V; Singh, R V; Sodhi, S.P.S (The Indian Journal of Animal Sciences, 2007)
Apparently healthy buffalo calves (10), 4 months to 1-year-old, were divided into 2 groups of 5 animals each and were subjected to i/v infusion of E. coli endotoxin @ 5 µg/kg BWl/ for 3 h and their acid-base and blood gas status was monitored. Group 1 animals, which acted as control were kept untreated and observed for next 4 h as well as after the end of endotoxin infusion revealed acidosis along with significant decrease in arterial PO2, increase in venous PO2 and PCO2. Endotoxin significantly decreased arterial 02, increase in venous PO2 and PCO2. Endotoxin significantly, decreased arterial 02 saturation while it significantly increased venous 02 saturation and blood bicarbonate. Group 2 endotoxemic buffalo calves, which were treated with i/v hypertonic saline solution (7.2% NaCl acq.) @ 4 ml/kg BW in 6.5 min revealed significant decrease in arterial base buffer during endotoxin infusion which increased significantly towards the end of observation period. Arterial and venous base excess, ECF base excess and arterial bicarbonate also showed significant increase. The arterial and venous pH, PO2, PCO2 and O2 saturation, venous base buffer and blood bicarbonate, all showed nonsignificant alterations which is suggestive of beneficial effects of hypertonic saline solution as it improves the circulation by drawing extracellular fluid into circulation, and the improved circulation improves the transport of 02 and removal of CO2 from tissues thereby preventing acidosis development.